Djibouti : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
In this paper, the first section provides statistical information of main sectors, namely the real, fiscal, monetary, and external sectors. This information supplements the data contained in the staff report for the Article IV Consultation. The second section provides a summary of the tax system of Djibouti. Real sector, GDP by sector of origin, supply and use of resources, agricultural production, slaughter and exports of animals and skins, and transportation activity are discussed. Government revenues, expenditures, and tax exemptions are also reviewed.